Aesthetic empowerment through music. (September 2019) - Brattico, Elvira; Varankaitė, Ulrika
This article describes how aesthetic enjoyment accompanying musical activities can empower individuals in health and disease. First, we explain the biological determinants of music enjoyment and how they can be studied. In doing so, we distinguish between core sensory pleasure and conscious liking, and we illustrate their respective contributions to aesthetic appreciation and expressive interaction with music. Second, we review findings illustrating the long-term impact of listening to favourite music on the brains of healthy musicians as well as on the brains and behaviour of individuals with pathological symptoms. Based on these findings, we propose a set of putative neural mechanisms underlying aesthetic empowerment through music. We also emphasize the importance of considering individual differences in sensitivity to aesthetic experiences of music, as evidenced, for instance, by neuroimaging and imaging genetics studies, drawing the connections between dopamine neurotransmission and dopaminergic genes with the reactivity of music–brain functions.